Political Psychology and the Possibility of Interdisciplinary Understanding of the Political Issue: A Critique on the Book Political Psychology - Aliashraf Nazari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The dynamic nature of political changes in the last two decades has led to a move towards new areas of science in order to understand and provide a realistic analysis of these changes. In the meantime, political psychology has attempted to bridge the gap between psychological, sociological, historical, philosophical, anthropological, and linguistic issues, in spite of the complexities that exist in different scientific fields, and to open new possibilities for reflection on political transformations. The expanding knowledge of political psychology with the multidisciplinary, dynamic, and applied nature has opened new horizons for those interested in presenting a new analysis of politics. The focus of the present paper is the introduction, critique and evaluation of the “Political Psychology” book, edited by John T Jost and Jim Sidanius in 2004 and published in New York by the Psychology Press. The main purpose of this article is methodological and theoretical analysis, critique, and evaluation of “Political Psychology” textbook.